PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 009 BINIO JAYA KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Armanita, Armanita; Kurniaman, Otang; Witri, Gustimal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : About problem which is found deep observational it which is its low usufructs student studying at brazes IV. SDN 009 Binio Dignities. Its low is yielding studies this student because of umpteen factor which is more teacher a lot of utilize discourse method, one that on its process student tends boring and less understand by just listen. That thing cause its reducing understanding student to a material teaches. Teacher just gets guidance by bind books, teacher as center as student studying so student activity less since more student a lot of listen explanation of teacher, method and learning model that insufficiently varies, and its reducing utilize studying media in processes teaching and learning, so creates saturation for deep student studies. Base about problem research do that action brazes with learnings model implement Inkuiri who aims to increase IPS'S studying result student brazes IV. SD Country 009 Binio School Year Dignity 2014/2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Inkuiri's Learning, therefore gets to increase IPS'S studying result student brazes IV. SDCountry 009 Binio Dignities on Technological formative material Production, Communication and Transportation. It can at see of acquired studying result student on base score which is with thoroughness percentage 43,75%, with average 61,56, worked up on i. cycle with thoroughness percentage 68,75% by average 72,96. Worked up again on cycle II. which is with thoroughness percentage 90,63% by average 80,93. Activity learns first cycle with percentage average 79,16% worked up as 94,16% on second cycle. Student activity on first cycle with percentage average 71,25% worked up as 88,75% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement Inkuiri can increase IPS'S studying result student brazes IV. SDN 009 Binio Dignities.Key word: Inkuiri, Learned result IPS